Role of Nursing Staff in the Humanized Delivery of Patients with COVID-19 - Gloria Medina Naranjo; Guadalupe Cuello Cuello; Adisnay Rodríguez Rodríguez; Riber Donoso Noroña (Medisur)
Background: childbirth and birth constitute universal human facts. To the usual insecurities during the act of birth today are added uncertainties derived from the COVID-19 pandemic. Objective: to identify the role of nursing staff in the humanized delivery of patients with COVID-19. Method: a descriptive and cross-sectional study was carried out at the General Hospital of Riobamba-Chimborazo, Ecuador, in the period from October 1 to 31, 2020. The study population consisted of the 5 nurses who work in the Gynecology and Obstetrics Service. The variables studied were: knowledge of the importance of providing a humanized delivery; assessment of the implementation of humanized childbirth and the reduction of maternal-fetal death; compliance with the regulations of humanized childbirth in time of COVID-19; training or self-training to provide humane treatment to pregnant patients diagnosed with COVID-19. The data was expressed in tables and graphs summarized in absolute frequencies and percentages. Results: 60 % knew the importance of providing a humanized delivery, 80 % considered that with the implementation of humanized delivery the maternal-fetal death had not decreased, 60 % stated that the regulations for humanized delivery in times of COVID-19. They were not met and 24 % stated that at the start of the pandemic they received training or self-trained to continue providing humane treatment to pregnant patients diagnosed with COVID-19. Conclusions: to promote the quality of care for the maternal-fetal binomial, it is important that the nursing staff is trained to cope with the situation.